2018
DOI: 10.3390/molecules23123172
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Arylidenechromanone/Flavanone Derivatives with Biological Macromolecules Studied as Human Serum Albumin Binding, Cytotoxic Effect, Biocompatibility Towards Red Blood Cells

Abstract: The aim of this study was to determine the cytotoxic effect of 3-arylidenechromanone (1) and 3-arylideneflavanone (2) on HL-60 and NALM-6 cell lines (two human leukemia cell lines) and a WM-115 melanoma cell line. Both compounds exhibited high cytotoxic activity with higher cytotoxicity exerted by compound 2, for which IC50 values below 10 µM were found for each cell line. For compound 1, the IC50 values were higher than 10 µM for HL-60 and WM-115 cell lines, but IC50 < 10 µM was found for the NALM-6 cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
(38 reference statements)
2
11
0
Order By: Relevance
“…Following on from a previous paper [10], the present study broadens our studies of the reactivity of 3-arylideneflavanones and 3-arylidenechromanone with diazomethane on a larger number of compounds containing various benzylidene substituents. The formation of spiro-compounds as a result of attack by a nucleophilic reagent on the carbon of the 3-arylideneflavanone most probably depends on the degree of electropositivity of the carbon; this would govern reactions with the various resonance structures of diazomethane [9].…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…Following on from a previous paper [10], the present study broadens our studies of the reactivity of 3-arylideneflavanones and 3-arylidenechromanone with diazomethane on a larger number of compounds containing various benzylidene substituents. The formation of spiro-compounds as a result of attack by a nucleophilic reagent on the carbon of the 3-arylideneflavanone most probably depends on the degree of electropositivity of the carbon; this would govern reactions with the various resonance structures of diazomethane [9].…”
Section: Introductionmentioning
confidence: 61%
“…Two structures, benzylideneflavanone and benzylidenechromanone substituted with diethylamine group, have been examined previously in a study that compared the exacytotoxic activity of the two compounds and checked whether they destroy erythrocyte membranes [10]. Encouraged by these positive results, the present manuscript examines the relationship between the biological activity of the tested compounds and their chemical structure: for this purpose ten 3-arylidenechromanone analogues with a ∆ 1 -pyrazoline ring were synthesized and their physicochemical characteristics, together with their cytotoxicity, determined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison of the logP value (theoretical) with the contribution of various contacts to the Hirshfeld surface found that theoretical lipophilicity (logP) is also inversely proportional to the percentage contribution of the CÁ Á ÁC contacts to the Hirshfeld surface. This analysis has been extended by similar flavonoid compounds and benzylidenochromanone derivatives available from our previous research (Kupcewicz et al, 2013;Adamus-Grabicka et al, 2018;Suchojad et al, The cytotoxic activity (expressed as log 1 IC 50 ) against the HL-60, NALM-6, WM-115 and COLO-205 cancer cell lines.…”
Section: Hirshfeld Surfacementioning
confidence: 99%